Fear of Death in the Epistle to the Hebrews - Holmes, Christopher T. (Review and expositor, 2022)
The fear of death is a topic frequently discussed in ancient sources, especially among moral philosophers. The mention of humanity’s enslavement to the fear of death in Heb 2:15 should be understood within this larger cultural and philosophical conversation. This article provides an overview of this larger discussion to understand better the reference to the fear of death in Hebrews. Along with this survey, the exemplary nature of Jesus’s death in Hebrews is decisive for understanding the fear of death in Hebrews.